2007
DOI: 10.1038/sj.ejhg.5201788
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of STOX1 as a preeclampsia candidate gene in a population-wide sample

Abstract: Preeclampsia is a common, pregnancy-specific vascular disorder characterised by hypertension and proteinuria. A recent report suggested association of the STOX1 gene on chromosome 10q22.1 with preeclampsia in the Dutch population. Here, we present a comprehensive assessment of STOX1 as a candidate gene for preeclampsia in the Finnish population by re-examining our previous genetic linkage analysis results for both chromosome 10 and paralogous loci, by genotyping representative markers in a nationwide data set,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 11 publications
1
26
0
5
Order By: Relevance
“…Moreover, the study of Berends et al (6), focusing on a ''familial'' subpopulation of samples, observed an association between STOX1 and the forms of pre-eclampsia with a strong familial component. In contrast, this polymorphism was not found to be associated with the disease in other populations where the pre-eclampsia was sporadic (31,37). Moreover, the imprinted status of STOX1 was questioned at the global placental level (31); whereas mono-allelic methylation and expression of this gene were detected in specific cell types of the placenta (extravillous column cytotrophoblasts) (70), and an independent study showed interindividual variation in the imprinting status of STOX1 (15).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study of Berends et al (6), focusing on a ''familial'' subpopulation of samples, observed an association between STOX1 and the forms of pre-eclampsia with a strong familial component. In contrast, this polymorphism was not found to be associated with the disease in other populations where the pre-eclampsia was sporadic (31,37). Moreover, the imprinted status of STOX1 was questioned at the global placental level (31); whereas mono-allelic methylation and expression of this gene were detected in specific cell types of the placenta (extravillous column cytotrophoblasts) (70), and an independent study showed interindividual variation in the imprinting status of STOX1 (15).…”
Section: Discussionmentioning
confidence: 99%
“…Die Mutationsträgerinnen erkrankten nur dann, wenn sie die Mutation von der Mutter geerbt hatten. Allerdings konnten 3 im Jahr 2007 veröffentlichte Studien zum STOX1-Gen die Beobachtungen von van Dijk et al [52] nicht bestätigen [53][54][55].…”
Section: Plazentationunclassified
“…Le rôle de STOX1 est maintenant controversé ; en particulier, la « mutation » découverte par les auteurs, Y153H, est en réalité très bien représentée dans de nombreuses populations humaines indemnes ; de plus, l'analyse transcriptionnelle du gène dans les placentas à terme ou proches du terme, montre que le niveau d'expression de STOX1 ne varie pas avec la pathologie placentaire. Finalement, même son statut de gène soumis à empreinte est maintenant remis en cause [9][10][11]. Des résultats récents de notre équipe semblent néanmoins suggérer que STOX1 pourrait quand même avoir un rôle clé dans les événements précoces du développement placentaire.…”
Section: Des Hypothèses Et Des Gènes Candidatsunclassified